2006
DOI: 10.1074/jbc.m506950200
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Membrane Ca2+-ATPase Isoform 4 Is Localized in Lipid Rafts of Cerebellum Synaptic Plasma Membranes

Abstract: Here we describe the association of the synaptosomal plasma membrane Ca 2؉ -ATPase (PMCA) from pig cerebellum with cholesterol/sphingomyelin-rich membrane domains (rafts). The PMCA4 was localized exclusively in rafts prepared by floatation in Nycodenz density gradients of ice-cold Brij 96 extracts. This was corroborated by its colocalization with the raft markers cholesterol, ganglioside GM1, and PrP C . The remaining PMCA isoforms were found in the detergent-soluble fractions, with the majority of the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 50 publications
2
68
1
3
Order By: Relevance
“…Cholesterol content from the gradient fractions was analyzed using a colorimetric assay (Sepú lveda et al, 2006) with minor modifications. Briefly, lipids were extracted by mixing 200 l of samples from each gradient fraction with 1 ml of chloroform/methanol (2:1), transferred to a glass tube and dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol content from the gradient fractions was analyzed using a colorimetric assay (Sepú lveda et al, 2006) with minor modifications. Briefly, lipids were extracted by mixing 200 l of samples from each gradient fraction with 1 ml of chloroform/methanol (2:1), transferred to a glass tube and dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…PMCA4 has also been observed to display a polarized expression pattern in kidney epithelial cells [81], and to communicate with mitochondria located in close proximity to the plasma membrane [82]. Finally, PMCA4 has recently been published to be specifically associated with lipid rafts in synaptic plasma membranes [83], whereas the PMCA1, 2 and 3 proteins were found in other membrane domains. Taken together these observations show, that despite their shared basic biochemical activity (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…The PMCAs are calmodulin-regulated enzymes that are essential for maintaining low intracellular calcium concentrations in the living cell [30,31]. Recent work has shown that PMCA isoforms and splice variants are active participants in localized Ca 2+ signaling, and that their targeting to and abundance at defined membrane sites must therefore be closely regulated [32][33][34][35]. All PMCA isoforms are expressed in the brain, with PMCA2 being abundant in several regions including the cerebellum, forebrain and hippocampus [28,36].…”
Section: Discussionmentioning
confidence: 99%